PELATIHAN BAHASA ISYARAT UNTUK PENGGERAK PKK DI KARANGPLOSO, MALANG - Prasetyia, Ferry; Pangestuty, Farah Wulandari; Kadji, Dzuliyati; Wijaya, Anorti Ika (Jurnal Abdi Insani, 2024)
A high prevalence of disability in Malang Regency prompted the Community Engagement  Team of FEB Universitas Brawijaya to initiate a program empowering people with disabilities to deliver sign language training. This community engagement  initiative aimed to enhance non-physical accessibility and inclusivity within community engagements. Specifically, it sought to improve communication skills between the general public and individuals with hearing impairments, ultimately facilitating their active participation in society. The program, conducted in collaboration with the Ngijo Village Government, targeted PKK activist as participants. Omah Gembira, a local community organization, partnered with the initiative by providing sign language training materials and involving individuals with hearing disabilities. The program encompassed three phases: planning, implementation, and evaluation. The sign language training successfully fostered participant enthusiasm and effectively equipped PKK activists with communication skills, leading to improved interactions with the hearing impaired. By promoting sign language proficiency, the training demonstrably contributed to improved non-physical accessibility and community inclusivity. Notably, the involvement of individuals with hearing disabilities in providing materials exemplifies the program's commitment to supporting their active participation. This community engagement  activity represents a positive step towards fostering a more inclusive society and encouraging the active involvement of people with hearing disabilities within the community.